2010
DOI: 10.1007/s10464-010-9398-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Neighborhood Factors on the Well-Being of Survivors of Intimate Partner Violence Over Time

Abstract: Intimate partner violence (IPV) is a pervasive social problem impacting the psychological well-being of millions of US women annually. The extant literature draws our attention to the devastating mental health effects of IPV, but largely overlooks how ecological factors may further explain survivors' well-being. This study examined how neighborhood disadvantage may contribute to survivors' compromised well-being, in addition to the abuse women experienced. Neighborhood disorder and fear of victimization signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 98 publications
3
17
0
Order By: Relevance
“…As noted by Beeble et al, however, previous studies in which researchers have examined ecological variables (vs. self-reported perceptions of neighborhoods) have sometimes failed to reveal links between neighborhood characteristics (defined, for example, by census blocks) and victims' clinical responses to violence, such as depression (e.g., community violence as studied by Curry, Latkin, & Davey-Rothwell, 2008). Such null findings have led researchers to caution against the application of objective measures of space in relation to clinical responses (Beeble et al, 2011).…”
Section: Empirical Articlementioning
confidence: 99%
See 1 more Smart Citation
“…As noted by Beeble et al, however, previous studies in which researchers have examined ecological variables (vs. self-reported perceptions of neighborhoods) have sometimes failed to reveal links between neighborhood characteristics (defined, for example, by census blocks) and victims' clinical responses to violence, such as depression (e.g., community violence as studied by Curry, Latkin, & Davey-Rothwell, 2008). Such null findings have led researchers to caution against the application of objective measures of space in relation to clinical responses (Beeble et al, 2011).…”
Section: Empirical Articlementioning
confidence: 99%
“…One of the few available studies of the proximal environments in which women live and of women's responses to IPA has illustrated the potential value of this line of inquiry. Using self-report methods, Beeble, Sullivan, and Bybee (2011) found that the inverse relationship between changes in women's perceptions of their neighborhoods' disorder over time and their quality of life was mediated through the women's fear. On the basis of these findings, Beeble et al suggested new points of potential intervention to support women subsequent to IPA exposure (e.g., programs to ensure access to safe housing options) as well as additional research on the environments in which women live and IPA.…”
Section: Empirical Articlementioning
confidence: 99%
“…All these factors contribute to elevate individuals' psychological distress. A recent study also describes how neighbourhood disorder, such as fighting, drug use, community conflicts, prostitution, and gang-related activity may increase partner violence and, in this way, augment individuals' psychological ill health and lower the overall quality of life (16).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to these conditions can lead to fear of victimization and mistrust (Ross & Jang, 2000). Neighborhood disorder is associated with trauma-related stress symptoms, increased risk for interpersonal trauma revictimization (Gapen et al, 2011; Obasaju, Palin, Jacobs, Anderson, & Kaslow, 2009), and depression (Blair, Ross, Gariepy, & Schmitz, 2014; Mair, Roux, & Galea, 2008), including among IPV survivors (Beeble, Sullivan, & Bybeee, 2011) and African American women (Cutrona et al, 2005). Perceived neighborhood disorder increases risk for hopelessness and suicide, controlling for individual-level sociodemographic variables (Denney, Wadsworth, Rogers, & Pampel, 2015; Mair, Kaplan, & Everson-Rose, 2012).…”
mentioning
confidence: 99%